“METHODOLOGICAL, TECHNOLOGICAL AND THEORETICAL FOUNDATIONS OF VOCAL EDUCATION INTEGRATED WITH GENERAL PROFESSIONAL MUSICAL SUBJECTS” - Norqobilov Asliddin Eshmamat og‘li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article analyzes the theoretical, methodological, and technological foundations of integrating general professional musical subjects into vocal education to enhance its content. The research reveals the role of subjects such as music theory, solfeggio, harmony, music history, and music literacy in developing students’ vocal competencies throughout vocal training. The pedagogical effectiveness of the integrative approach, its impact on the development of vocal technique, and its potential to support students’ creativity are examined from a scientific and theoretical perspective. The article also highlights the advantages of using modern information technologies, multimedia tools, audio-visual analysis methods, and innovative methodological platforms in vocal lessons.